2007
DOI: 10.1074/jbc.m701057200
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Modeling of Matrix Vesicle Nucleation

Abstract: Annexins A5, A2, and A6 (Anx-A5, -A2, and -A6) are quantitatively major proteins of the matrix vesicle nucleational core that is responsible for mineral formation. Anx-A5 significantly activated the induction and propagation of mineral formation when incorporated into synthetic nucleation complexes made of amorphous calcium phosphate (ACP) and Anx-A5 or of phosphatidylserine (PS) plus ACP (PS-CPLX) and Anx-A5. Incorporation of Anx-A5 markedly shortened the induction time, greatly increasing the rate and overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 71 publications
1
74
0
Order By: Relevance
“…We found that all of the tested purified native human (Anx-H5) and avian annexin-A5 (Anx-A5) samples strongly stimulated mineral formation by PS-CPLX (45). For this study, we used both native chicken liver Anx-A5 and native human placental Anx-H5, which had comparable activity.…”
Section: Synthesis Of Acp Cplx and Anx-a5-containingmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that all of the tested purified native human (Anx-H5) and avian annexin-A5 (Anx-A5) samples strongly stimulated mineral formation by PS-CPLX (45). For this study, we used both native chicken liver Anx-A5 and native human placental Anx-H5, which had comparable activity.…”
Section: Synthesis Of Acp Cplx and Anx-a5-containingmentioning
confidence: 99%
“…Using a variety of analytical methods (17,18,41,42), this core has been shown to contain three main components as follows: 1) amorphous calcium phosphate (ACP); 2) membrane-associated CPLXs; and 3) annexins-A5, -A6, and -A2. Recently we documented the remarkable enhancement that annexin-A5 has on mineral formation by biomimetic nucleational complexes (45, 46).…”
Section: Matrix Vesicles (Mvs)mentioning
confidence: 99%
See 3 more Smart Citations